Empowering Women’s Groups through Vegetable-Based Product Diversification Innovations in Aia Tajun Village - Rahmi Awalina; Wellyalina Wellyalina; Risa Meutia Fiana; Reni Koja; Nika Rahma Yanti; Putri Wulandari Zainal; Omil Charmyn Chatib (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2026)
This outreach activity aims to enhance the capacity and economic self-reliance of women’s groups through vegetable-based product diversification innovations in Nagari Aia Tajun, Lubuk Alung Subdistrict, Padang Pariaman Regency. The method employed was a participatory approach involving the administration of a pre-test questionnaire, educational sessions, hands-on training, and an evaluation using a post-test. The innovative product developed is a vegetable-based healthy beverage in the form of water spinach smoothies as a way to utilize local potential. The results of the activity show a significant improvement in the participants’ knowledge, skills, and entrepreneurial attitudes, with the average score increasing from 2.1 to 4.26 and an N-Gain value of 0.74 (high category). Additionally, this activity successfully boosted participants’ interest and self-confidence in developing businesses based on processed vegetable products. Thus, this program not only contributes to increasing the value-added of agricultural commodities but also supports the strengthening of community economies and local food security through women’s empowerment.